ECRG4 Represses Cell Proliferation and Invasiveness via NFIC/OGN/NF-κB Signaling Pathway in Bladder Cancer - Liang, Xin; Gao, Jiangang; Wang, Quan; Hou, Sichuan; Wu, Changli (Frontiers in Genetics, 2020)
Bladder cancer (BCa) is a malignant tumor in the urinary system with high cancer-related mortality worldwide. However, the molecular mechanisms of many genes dysregulated in BCa are still unclear. Herein, we showed that esophageal cancer-related gene-4 (ECRG4), which is downregulated in BCa tissues and cell lines, has a positive correlation with osteoglycin (OGN). Further functional experimental studies suggested that both ECRG4 and OGN inhibit cell proliferation, migration, and invasion in BCa cells. Moreover, ECRG4 acts as a tumor repressor and promotes the expression of OGN via the upregulation of nuclear factor 1 C-type (NFIC), which can bind to the promoter region of OGN and regulate its transcription. Bioinformatics analysis revealed that NFIC is downregulated in BCa tissues and has a positive correlation with ECRG4 or OGN. Esophageal cancer-related gene-4 could positively regulate the protein levels of NFIC in BCa cells. In addition, we demonstrated for the first time that ECRG4 inhibits the nuclear factor (NF)-κB signaling pathway via the upregulation of OGN in BCa cells. Overall, these findings provide evidence that both ECRG4 and OGN function as tumor repressors and that overexpression of ECRG4 inhibits the NF-κB signaling pathway by promoting NFIC/OGN signaling in BCa cells. Our results reveal the molecular regulatory mechanisms of the ECRG4-mediated repression of the NFIC/OGN/NF-κB signaling pathway in BCa and provide potential biomarkers or therapeutic targets for BCa.